More than meets the eye [compact disc, unabridged] - Johansen, Iris; Johansen, Roy (Johansen, Iris. Kendra Michaels series, 2023)
Iris Johansen and Roy Johansen team up for another page-turning thriller as investigator Kendra Michaels is drawn into the FBI's case against a prolific serial killer who is about to reveal the location of his numerous victims.